Generación del 27/ hip hop in 2007: cultural vanguard in performance - Cunha, Roseli Barros; Rondinelli, Marcelo (Acta Scientiarum. Language and Culture, 2015)
This paper discusses the production of the so-called Generation of 27 and the documentary Generación 27 - Creación, vanguardia y vida, Canal Sur Andalucia, Spain, in honor of the 80 years of the movement. We address the performance matter, according to the theory by Zumthor (2000), which can be compared to what the participants of that generation did during that period in their artistic encounters, and in a parallel way to what some artists that express themselves through rap and graffiti did in 2007, by resuming the poetic, musical and visual creations of the artists of 1927. We develop a comparative analysis of these productions and of what participants of the Spanish movement (ALONSO; GUILLÉN, 1984) and literary historians (CONCHA, 1984) argue about the period, and of authors (REYES-SÁNCHEZ, 2007; HALL, 2011) who research the cultural manifestations that are closer to the new global social reality. We conclude that both movements, Generation of ‘27 and the artists of 2007, seek, with their productions, to give visibility to the plurality of voices of the popular and street tradition, even though the documentary suggests the presence of a hegemonic and institutional apparatus that somehow interacts and interferes with the maintenance and / or expansion of this process.